Strategies for countering radicalism in teaching of islamic religious education at smkn bansari - Tuti Amalia; Husna Nashihin; Sigit Tri Utomo (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This study aims to investigate the Islamic Religious Education (PAI) learning strategies at SMKN Bansari. A qualitative method was employed, with data collected through participant observation, semi-structured interviews, and document analysis. Data processing techniques included description, reduction, and conclusion drawing. The research findings indicate that SMKN Bansari implements counter-radicalism strategies in several ways. These include integrating moderate values into the curriculum, specifically the values of Ahlussunnah Wal Jamaah An-Nahdliyyah (Aswaja An-Nahdliyyah). These values encompass tasamuh (tolerance), I’tidal (justice), tawazzun (balance), and tawasuth (equality). These values are integrated not only as memorization but as a guide to life. SMKN Bansari also implements routine habits and PAI learning programs that strengthen students' moderate character. These activities include reading the Al-Qur'an before lessons, praying before and after learning, and practicing good behavior spontaneously. Specific practices include greeting teachers, maintaining politeness, disposing of waste properly, queuing, respecting the opinions of others, asking permission to enter/exit, and helping others. Programmed activities include class meetings and Pesantren Kilat (intensive religious programs).